1976
DOI: 10.1177/00220345760550051001
|View full text |Cite
|
Sign up to set email alerts
|

Stress Analysis of Porous Rooted Dental Implants

Abstract: A model based on a continuously bonded interface predicts high punching stresses at the apex of the implant and low stresses in the cortical plates. A model based on a continuously bonded interface predicts high stiffness and a resultant low implant displacement-load ratio. A model based on a tissue ingrowth-bonded interface predicts uniform distribution of stresses around the implant through the cortical plates. A model based on a tissue ingrowth-bonded interface predicts an implant displacement-load ratio cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
7

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 2 publications
0
52
0
7
Order By: Relevance
“…[41] Stress distribution is performed in an implant which has a place with single tooth to know the impact of parameters and geometry of the implant. [42][43][44] 3D investigation of FEA performed by Borchers and Reichart. [45] The foremost trouble in recreating the mechanical conduct of dental inserts is the displaying of human bone tissue and its reaction to connected mechanical device.…”
Section: Role Of Fea In Biomechanical Systemmentioning
confidence: 99%
“…[41] Stress distribution is performed in an implant which has a place with single tooth to know the impact of parameters and geometry of the implant. [42][43][44] 3D investigation of FEA performed by Borchers and Reichart. [45] The foremost trouble in recreating the mechanical conduct of dental inserts is the displaying of human bone tissue and its reaction to connected mechanical device.…”
Section: Role Of Fea In Biomechanical Systemmentioning
confidence: 99%
“…A tapered design made of a material with high elastic modulus was concluded to be the most suitable design in their study. Weinstein et al (1976) investigated a porous rooted dental implant and concluded that high bone-level stresses are induced near the apex of the implant in a model with continuously bonded interface. In their comparative evaluation of five commercially available implant systems, Bozkaya et al (2004) showed that implant systems with internally sloping crestal modules are better at reducing the bone overload in the cortical bone, whereas systems with widening crestal-modules cause bone overload in compression.…”
Section: Implant-contourmentioning
confidence: 99%
“…The key factors for the success or failure of dental implants is the manner in which stresses are transferred to the surrounding bone [17].…”
Section: Introductionmentioning
confidence: 99%